Breaking the Foreign Language Barrier with Writing Gerald S. Giauque. - Giauque, Gerald S. (Distributed by ERIC Clearinghouse, 1976)
Second language students are often discouraged in trying to acquire oral fluency skills. Four specific problem areas are: (1) timidity; (2) listening comprehension difficulties; (3) oral reading problems; and (4) difficulty in putting sentences together. An approach that emphasizes writing skills avoids these problem areas and uses skills the students already possess in their native language. An exercise in which students are asked to write what they say as they speak in their native language helps the students visualize words with greater facility. In the next step, students write their speech as they speak in the target language. Parallel to this activity, students should practice writing in the target language. (AM)